2016
DOI: 10.1111/acem.13015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Direct and Video‐assisted Laryngoscopy for Intubations in a Pediatric Emergency Department

Abstract: Objectives: The objective was to compare video-assisted laryngoscopy (VAL) to direct laryngoscopy (DL) on success rate and complication rate of intubations performed in a pediatric emergency department (ED).Methods: This is a retrospective cohort study of attempted intubations of children aged 0-18 years in a pediatric ED between 2004 and 2014 with first attempt by an ED provider. In VAL, the laryngoscopist attempts direct visualization of the glottis with a C-MAC video laryngoscope while the video monitor is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 37 publications
(57 reference statements)
3
37
0
Order By: Relevance
“…[ 9 ] Kerrey et al's study, which reported a 64% (48/75) first-attempt intubation success rate using VL, was used to estimate the possible effect of this intervention, which was an increment of 25% from the first-attempt intubation success rate (64%–39%). [ 12 ] Considering a statistical power of 80%, significance of 95%, 2-tailed t test, and 94 cases in the first group, the 46 cases in the study group should demonstrate a 25% increase in the first-attempt intubation success rate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 ] Kerrey et al's study, which reported a 64% (48/75) first-attempt intubation success rate using VL, was used to estimate the possible effect of this intervention, which was an increment of 25% from the first-attempt intubation success rate (64%–39%). [ 12 ] Considering a statistical power of 80%, significance of 95%, 2-tailed t test, and 94 cases in the first group, the 46 cases in the study group should demonstrate a 25% increase in the first-attempt intubation success rate.…”
Section: Methodsmentioning
confidence: 99%
“…The laryngoscopist initially attempted a direct visualization of the glottis using a C-MAC video laryngoscope (Karl Storz, Germany), whereas the video screen was used by a supervisor for real-time guidance. [ 12 ] Similarly, Kerrey et al used the C-MAC video laryngoscope as the first device for pediatric intubation with providers performing intubation with DL and a “copilot” attending physician watching the video screen. This strategy reached a first-attempt intubation success rate of 64% on a filmed intubation review.…”
Section: Introductionmentioning
confidence: 99%
“…Varghese and Kundu, evaluating intubation among twenty children aged 1-24 months, indicated that the Miller and the Macintosh blades provide similar laryngoscopic views and intubating conditions. Verghese and Kundu's study showed that [22]. In turn, Hippard et al showed higher success rates and shorter intubation times with the Miller blade compared to either videolaryngoscope which may reflect one's greater experience in direct laryngoscopy [23].…”
Section: Discussionmentioning
confidence: 97%
“…As shown by Long et al in a paediatric emergency department, the overall first-pass success rate was 78%, although first-pass success without desaturation or hypotension was only 49% [7]. In turn, studies by Eisenberg et al indicate the effectiveness of the first intubation attempt at the level of 71% [8], while the study by Pallin et al showed 83% [9]; however, in the above studies the intubation was performed by emergency physicians or anaesthesiologists. In out-of-hospital conditions or in a situation where intubation is performed by less experienced personnel, the effectiveness of intubation can range from 63.4% to 78.6% [10][11][12].…”
Section: Introductionmentioning
confidence: 91%